Towards resilient, inclusive, sustainable livestock farming systems - Bilotto, Franco; Harrison, Matthew T.; Vibart, Ronaldo; Mackay, Alec; Christie-Whitehead, Karen M.; Ferreira, Carla S.S.; Cottrell, Richard S.; Forster, Daniel; Chang, Jinfeng (Elsevier, 2024)
Background While livestock products comprise the cornerstone of food security, livestock managers face the dual challenge of adapting to a climate crisis and sustainably reducing greenhouse gas emissions. Climatic variability and extreme weather events impact the agri-food chain, hindering global agricultural productivity and threatening safe, nutritious, and affordable livestock products. Scope and approach This review delves into five key aspects: (1) the cultural, socio-economic, and food security importance of livestock, (2) the impact of climatic, economic, and geopolitical shocks on the global livestock sector, (3) the livestock sector's role in climate change, (4) opportunities for transitioning to inclusive, sustainable livestock farming systems, and (5) prerequisites and transformative initiatives for the livestock sector. Key findings and conclusions Climatic, economic, and geopolitical shocks have increased, particularly affecting the poultry, dairy, and small ruminant sectors in the last three decades. These shocks have amplified risks of contravening tipping points. Low adaptive capacity and high vulnerability to the climate emergency demand place-based adaptation. Interventions reducing food waste and restoring tropical forests offer the greatest mitigation potential, while agrivoltaics and on-shore wind production appear most promising economically. Trade-offs between production, conservation, prosperity, and mitigation demand contextualization and co-design of innovations for credibility, legitimacy, and adoptability.
Keywords: environmental stewardship; land custodianship; adaptation; extreme events; shocks; global financial crisis